Growth of mica porphyroblasts under low-grade metamorphism – A Taiwanese case using in-situ40Ar/39Ar laser microprobe dating. (November 2016) - Chen, Chih-Tung; Chan, Yu-Chang; Lo, Ching-Hua; Lu, Chia-Yu
Abstract: Mica porphyroblasts, a common metamorphic microstructure, are analyzed in the slate belt of northern Taiwan where large fish-like growths are found within a meta-pyroclastics. With constraints on the time-temperature history from deposition through peak metamorphic state to exhumation, in-situ 40 Ar/ 39 Ar laser microprobe dating was carried out on muscovite and corrensite fibers of mm-scale mica porphyroblasts grown on a pressure-solution seam. Because the peak metamorphic temperature and the porphyroblast formation condition (∼250 °C) remained far below the closure temperature of the K-Ar radioisotope system in muscovite, and the absence of muscovite in the mafic protolith, the dating results likely document the growth of the mica porphyroblast fabrics. The syn-kinematic nature of the analyzed porphyroblasts is confirmed by the ∼6 to ∼2.5 Ma growth ages, suggesting that the host rock was continuously deformed during the earlier two-thirds of the Taiwan Orogeny. The pattern of fiber growth, in contrast to outward-decreasing ages normally observed in peripheral recrystallization, appears random and resembles void fills in boudin openings. We postulate that syntaxial crack-seal following tensile micro-boudinage, along with slips on sub-grain boundaries, as a viable mechanism for the development of mica porphyroblasts and fish especially in lower-grade metamorphic rocks. Highlights: Growth of mica porphyroblast documented by in-situ 40 Ar/ 39 Ar dating. Protracted porphyroblast development related to underplating in Taiwan orogeny. Crack-seal between micro-boudins of mica explains the growth age distribution.